Sistem Pencatatan Keuangan Aplikasi Android Dengan Menggunakan Design Pattern Model-View-View-Model (MVVM), Room Database, SharedPreference dan API. - Naufal Rasyid; Aaqila Dhiyaanisafa Goenawan (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2022)
Most of people in the world are familiar with smart phones or smartphones, and because of their very complete and practical uses, smartphone users are always increasing every year. Smartphones are used for various types of activities such as for social media, for entertainment such as playing games, doing office work, even personal matters such as financial management applications. Therefore, an application was created that can support personal financial recording so that it can make it easier for users.